Odpowiedzi

2010-02-04T18:10:22+01:00
Zad1
a)3(4x-2)-2(x-3)=10
12x-6-2x+6=10
10x=10
x=1

b)(3x+4)x+3x=11+3x²-4
3x²+4x+3x=7+3x²
7x=7
x=1

zad2
a)X+y =20
2x+3y=52

x=20-y
2x+3y=52

x=20-y
2*(20-y)+3y=52

x=20-y
40-2y+3y=52

x=20-y
y=12

x=20-12
y=12

x=8
y=12
b)2x+y=16
5x-6y=0

y=16-2x
5x-6*(16-2x)=0

y=16-2x
5x-96+12x=0

y=16-2x
17x=96

y=16-2x
x=96/17

y=16-2*(96/17)
x=96/17

y=16-192/17
x=96/17

y=272/17-192/17
x=96/17

x=80/17
x=96/17
Najlepsza Odpowiedź!
2010-02-04T18:12:25+01:00
Zad.1
a) 3(4x-2)-2(x-3)=10
12x-6-2x+6=10
12x-2x=10+6-6
10x=10
x=1
b) (3x+4)x+3x=11+3x²-4
3x²+4x+3x=11+3x²-4
3x²+7x-3x²=7
7x=7
x=1

zad.2
a) x+y=20//*(-2)
2x+3y=52
-2x-2y=-40
2x+3y=52
y=12
x=8

b)2x+y=16//*6
5x-6y=0
12x+6y=96
5x-6y=0
17x=96
x=96/17
y=80/17